PATTERN OF INJURIES SEEN IN MASS CASUALTIES IN TERRORIST ATTACKS IN BALUCHISTAN, PAKISTAN - A THREE YEARS EXPERIENCE - Maqsood, Rasikh; Rasikh, Alia; Abbasi, Tariq; Shukr, Irfan (Journal of Ayub Medical College Abbottabad, 2015)
Background: As a front line state in war against terror, Pakistan has been a victim of terrorism, for the last many years & Baluchistan has been the hub of all such terror activities. The objective of this study was to determine the incidence and type of injuries in mass casualties in terrorist activities in Baluchistan. Methods: The study was done by the review of the record of all patients of terrorist attacks who were admitted in Combined Military Hospital (CMH) Quetta from 27th Aug 2012 to 31st Jul 2015. The final injuries sustained by the victims were documented in the patient charts after repeated examination. The data was collected from these patient charts. Data was analysed using SPSS-21. Frequency & percentages of different injuries was calculated to determine the injury pattern. Results: A total of 3034 patients reported to the hospital (n-3034), 2228 were admitted (73.4%). Out of the injured, 1720 (56.69%) were patients of multi system trauma, whereas 1314 (43.3%) had a single site injury. Out of these 537 patients had fractures of long bones (17.6%), those with head & spinal injuries with neurological deficit were 455 (14.9%), 266 had abdominal injuries requiring surgical intervention (8.7%), 75 (2.47%) had thoracic injuries were whereas 25 (0.82%) were vascular injuries, requiring emergent limb saving surgeries. Sex ratio was M/F=5.7: 1 Mean hospital stay was 6.31 days. Conclusion: Majority of the injured had multisystem injuries; therefore the hospital should have a well-trained multi-disciplinary team of surgeons. In addition to general surgery, the subspecialties’ should include orthopaedics, vascular, thoracic and neurosurgery.